2018
DOI: 10.1186/s12860-018-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Contactin 1 promotes growth, migration and invasion in Hs578T breast cancer cells

Abstract: BackgroundContactin1 (CNTN1) has been shown to play an important role in the invasion and metastasis of several tumors; however, the role of CNTN1 in breast cancer has not been fully studied. The purpose of this study is to investigate the role of CNTN1 in regulating tumor growth, migration and invasion in breast cancer.ResultsTo investigate its function, CNTN1 was expressed in Hs578T cells. CNTN1 expression was confirmed by western blot, immunohistochemistry and real-time RT-PCR. The effect of CNTN1 overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Future directions in interrogating metastatic effects of ERK5 expression in breast cancer using intracardiac injections would incorporate examining bone and brain metastases (53). Furthermore, consistent with current literature, Hs-578T xenografts are minimally invasive in vivo (54), which may explain the lack of contrast in metastatic potential between control and ERK5-ko tumors.…”
Section: Discussionmentioning
confidence: 73%
“…Future directions in interrogating metastatic effects of ERK5 expression in breast cancer using intracardiac injections would incorporate examining bone and brain metastases (53). Furthermore, consistent with current literature, Hs-578T xenografts are minimally invasive in vivo (54), which may explain the lack of contrast in metastatic potential between control and ERK5-ko tumors.…”
Section: Discussionmentioning
confidence: 73%
“…CNTN-1, mapped to the chromosome 12q11-q12 region and composed of six C2 Ig-like repeats and four fibronectin type III (FNIII) domains, is the first identified member of the CNTN family of neural cell-recognition molecules 43,44 . CNTN-1 is an essential molecule in nervous system development and has been reported to be associated with metastasis, proliferation and drug resistance in gastric cancer 45 , thyroid cancer 46 , breast cancer 32 , HCC 47 and lung adenocarcinoma 48 . In line with previous investigations, we observed that expression of CNTN-1 in resistant cells was higher than in progenitor cells, suggesting cancer stem cell-like characteristics with higher migration ability and anoikis resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has revealed that CNTN-1 is involved in carcinogenesis and cancer progression 30,31 . For example, overexpression of CNTN-1 promotes cell proliferation, colony formation and migration in breast cancer 32 . And inhibition of CNTN-1 in lung adenocarcinoma has been shown to abolish tumor metastasis and prolong survival in a xenograft model 33 .…”
Section: Introductionmentioning
confidence: 99%
“…3D). CNVs in AIS involved genes related to cell adhesion and growth, 30,31 including significantly higher copy number gain of EGFR, whereas in MIA and IAC, CNVs more commonly affected genes associated with metastasis and invasion [32][33][34][35][36] (see Fig. 3D).…”
Section: Intertumoral Heterogeneity and Mutation Spectrummentioning
confidence: 98%